2014
DOI: 10.1017/s0317167100018436
|View full text |Cite
|
Sign up to set email alerts
|

Neurophobia Inception: A Study of Trainees' Perceptions of Neurology Education

Abstract: Objectives:We wanted to examine the extent to which “neurophobia” exists among medical students and determine if students’ perceptions of neurology differ by year of study while exploring the factors that contribute to the development of “neurophobia”.Methods:We used a two-phase, sequential, mixed-methods explanatory design in this single centre study. Phase 1 involved the collection and analysis of a questionnaire administered to students in the first three years of medical school. Phase 2 involved focus grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 15 publications
5
61
0
4
Order By: Relevance
“…Overall, neuroanatomy is consistently cited as one of the most challenging portions of the anatomical sciences curriculum by medical students and junior physicians alike (Jilwan et al, ). Further evidence from the literature suggests that this poor understanding of neuroanatomy leads to a dislike or fear of the subject in clinicians and trainees (Schon et al, ; Flanagan et al, ; Ridsdale et al, ; Lim and Seet, ; Hudson, ; Youssef, ; Sanya et al, ; Zinchuk et al, ; Gupta et al, ; Kam et al, ; Matthias et al, ; Fantaneanu et al, ; McCarron et al, ; Pakpoor et al, ; Abushouk and Duc, ). The term “neurophobia” was first coined by Jozefowicz to describe this fear of the neural sciences and their clinical application in neurology (Jozefowicz, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, neuroanatomy is consistently cited as one of the most challenging portions of the anatomical sciences curriculum by medical students and junior physicians alike (Jilwan et al, ). Further evidence from the literature suggests that this poor understanding of neuroanatomy leads to a dislike or fear of the subject in clinicians and trainees (Schon et al, ; Flanagan et al, ; Ridsdale et al, ; Lim and Seet, ; Hudson, ; Youssef, ; Sanya et al, ; Zinchuk et al, ; Gupta et al, ; Kam et al, ; Matthias et al, ; Fantaneanu et al, ; McCarron et al, ; Pakpoor et al, ; Abushouk and Duc, ). The term “neurophobia” was first coined by Jozefowicz to describe this fear of the neural sciences and their clinical application in neurology (Jozefowicz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies focused mainly on clinical neurology and alluded to an impaired understanding of neuroanatomy in the broader context of difficulties associated with practicing clinical neurology. In particular, Fantaneanu and colleagues identified a number of modifiable (such as timing of delivery) and unmodifiable (such as past exposure or preconceptions) risk factors associated with the onset of neurophobia and suggest acting on modifiable ones to reduce its prevalence (Fantaneanu et al, ). Moreover, while a comprehensive survey revealed very few positive outcomes (McColgan et al, ), potential strategies to reduce neurophobia have started to emerge from systematic studies (McColgan et al, ; Abushouk and Duc, ).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] One potential factor contributing to this is a phenomenon coined "neurophobia," a perceived reluctance of medical students to learn or relearn neuroanatomy. [15][16][17][18][19] In an effort to diminish neurophobia and improve spatial and 3-dimensional neuroanatomy learning, 3-dimensional strategies have been proposed. 3,[20][21][22] Several studies have shown that 3-dimensional neuroanatomical learning is an effective strategy for increasing neuroanatomical knowledge, motivation and retention of neuroanatomy material.…”
mentioning
confidence: 99%
“…The methodology used in this study is new in the field of neurological pedagogic research [33]. A content analysis is considered a useful tool for examining trends and patterns and provides a basis for monitoring shifts in attitudes [19, 20] and it is also a powerful data-reduction technique.…”
Section: Discussionmentioning
confidence: 99%